2002
DOI: 10.1242/jcs.115.5.1059
|View full text |Cite
|
Sign up to set email alerts
|

Ephrin-A5 induces rounding, blebbing and de-adhesion of EphA3-expressing 293T and melanoma cells by CrkII and Rho-mediated signalling

Abstract: Eph receptor tyrosine kinases and ephrins regulate morphogenesis in the developing embryo where they effect adhesion and motility of interacting cells. Although scarcely expressed in adult tissues, Eph receptors and ephrins are overexpressed in a range of tumours. In malignant melanoma, increased Eph and ephrin expression levels correlate with metastatic progression. We have examined cellular and biochemical responses of EphA3-expressing melanoma cell lines and human epithelial kidney 293T cells to stimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(15 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…Phosphorylation of cytoplasmic tyrosine residues is a hallmark of Eph receptor activation and downstream signaling . Like other Eph receptors, wild-type EphA3 is constitutively tyrosine phosphorylated when overexpressed by transient transfection in HEK 293 cells (Figure A). Interestingly, we found that four of the eight mutations examined in the EphA3 kinase domain [R728L, K761N, G766E, and D806N (Figure )] essentially abolish EphA3 tyrosine phosphorylation in HEK 293 cells (Figure A and Table ). This effect is similar to that of the K653R control mutation, which disrupts ATP binding .…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…Phosphorylation of cytoplasmic tyrosine residues is a hallmark of Eph receptor activation and downstream signaling . Like other Eph receptors, wild-type EphA3 is constitutively tyrosine phosphorylated when overexpressed by transient transfection in HEK 293 cells (Figure A). Interestingly, we found that four of the eight mutations examined in the EphA3 kinase domain [R728L, K761N, G766E, and D806N (Figure )] essentially abolish EphA3 tyrosine phosphorylation in HEK 293 cells (Figure A and Table ). This effect is similar to that of the K653R control mutation, which disrupts ATP binding .…”
Section: Resultsmentioning
confidence: 77%
“…The EphA3 receptor is widely expressed during embryonic development, with the highest levels occurring in the nervous system and heart. EphA3 is expressed at lower levels in some adult tissues, such as the brain, lung, bladder, prostate, and colon. , The best characterized roles of EphA3 thus far are in the epithelial–mesenchymal transition in the developing heart , and in axon guidance in the developing nervous system, where this receptor plays a repulsive role that causes axons to avoid regions of strong ephrin ligand expression. EphA3-dependent retraction of cellular processes has also been reported in non-neuronal cells . However, there is only limited information about the signal transduction pathways triggered by EphA3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activated RAS (RAS-GTP) regulates multiple cellular functions through effectors including Raf, phosphatidylinositol 3-kinase (PI3K), and Ral guanine nucleotide-dissociation stimulator (RALGDS) 38 41 . EFNA5 is the Eph receptor on the cell surface, a family of receptor tyrosine kinases, which plays an important role in migration and adhesion during the development of neurons, blood vessels and epithelium 42 , 43 . FGF3 and FGF8 are involved in the regulation of embryonic development, proliferation, differentiation and migration, and are required for normal brain, eyes, ears and limb development during embryogenesis 44 48 .…”
Section: Discussionmentioning
confidence: 99%